Pengaruh Jumlah Omset dan Sanksi terhadap Kepatuhan Wajib Pajak Hotel, Restoran, dan Hiburan di Kota Medan - Annisa Fajaria; Zuhrinal M. Nawawi (VISA: Journal of Vision and Ideas, 2022)
Medan as one of the largest metropolitan cities in Indonesia, of course, should pay more attention to public compliance with payments and taxes, especially in this case the hotel, restaurant and entertainment tax in Medan. This study aims to determine how turnover and fines affect compliance with tax regulations, hotels and entertainment in the city of Medan. This research was conducted by using a literature search research method and using secondary data. The results showed that the imposition of fines together with the imposition of fines had a significant effect on compliance with hotel, restaurant, and entertainment taxpayer regulations in Medan. While the amount of revenue received does not affect taxpayer compliance with hotels, restaurants, and entertainment in the city of Medan. Keywords: Hotel Tax, Restaurant Tax, Entertainment Tax, Taxpayer Compliance